(untitled) - Luby, Brittany; Donovan, Natasha (New York, 2023)
After his family moves to the city, young Ojiig misses the life he knew back home and the night sky full of stars until his parents help him find ways to make the city feel more like home.
Ages 4-8.
Keywords: Fiction; Ojibwa Indians; Fiction; Ojibwa Indians; Fiction; Stars; Indians of North America; Fiction; Juvenile fiction; Juvenile fiction; Indians of North America; Juvenile fiction; Stars; Juvenile fiction; Moving, Household; Moving, Household; Picture books